2019
DOI: 10.1097/ncq.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Symptom Management Patient Education for People With Acute Coronary Syndrome

Abstract: Background: Poorly managed acute coronary syndrome symptoms increase the risk of subsequent cardiovascular events. Purpose: The aim of this study was to evaluate the effectiveness of symptom management patient education on the knowledge of sublingual nitroglycerin for people with acute coronary syndrome. Methods: A randomized controlled trial was used to evaluate the 3-resource intervention. The study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Cardiac education is pivotal to ensure that patients become aware of their chronic condition of heart disease (Stolic, Lin, & Mitchell, 2019); however, research has shown that some patients undergoing PCI experienced overwhelming wellness and believed that they were cured of CHD (Carroll, 2005;Young & Barnason, 2014). The reasons for this health misconception might be varied, including staff factors such as staff' advising that they try to "fix" the blockage or patient factors such as patients'…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac education is pivotal to ensure that patients become aware of their chronic condition of heart disease (Stolic, Lin, & Mitchell, 2019); however, research has shown that some patients undergoing PCI experienced overwhelming wellness and believed that they were cured of CHD (Carroll, 2005;Young & Barnason, 2014). The reasons for this health misconception might be varied, including staff factors such as staff' advising that they try to "fix" the blockage or patient factors such as patients'…”
Section: Discussionmentioning
confidence: 99%
“…The total scores range from 0 to 28, which means the higher scores, the better methodological quality of the study. The study was categorized based on following cutoff points: Excellent (26)(27)(28), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19), and poor (≤14) based on the United States Preventive Services Task Force approach [16].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Nineteen studies were conducted across 11 countries, they were 13 in Asia (Iran: 6, Saudi Arabia: 1, Thailand: 1, Hong Kong: 1, China: 2, Korea: 1, and Jordan: 1), 5 in Europe (Ireland: 1, Czech Republic: 1, and Turkey: 3) and Australia (1). Among them, 12 studies were conducted as randomized controlled trial [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28]. The patient populations included adults hospitalized for first-time myocardial infarction, either with ST-segment elevation or with no ST-segment elevation and either had or not had percutaneous coronary intervention.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations